2007
DOI: 10.1111/j.1399-3054.2007.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on the expression of aluminium toxicity in Phaseolus vulgaris

Abstract: The interaction of boron (B) and aluminium (Al) was investigated in 5-day-old seedlings of soybean cv. Maple Arrow. Al treatment inhibited root elongation and callose formation in root tips particularly after 4-h Al treatment. After 10 and 24 h, both parameters indicated increasing recovery from Al stress. B deficiency aggravated Al toxicity compared with B sufficiency. B deficiency did lead to an increase in unmethylated pectin in the first 3 mm of the root tip. This increase in potential binding sites is ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 34 publications
5
48
0
Order By: Relevance
“…Beans differ from cereals by being quiescent when Al treatment begins and later expressing tolerance components (Cumming et al, 1992;Rangel et al, 2007). That is, beans demonstrate a type II response pattern to Al treatment (Ma et al, 2001), which is characterized by a delay of several hours before organic acids, particularly citric acid, are exuded (Mugai et al, 2000;Shen et al, 2002aShen et al, , 2002bShen et al, , 2004Stass et al, 2007). Recently, Rangel et al (2009) demonstrated that apoplastic Al induces the inhibition of root elongation and that recovery from the stress caused by this element is controlled by reducing Al in the apoplast, thus permitting renewed elongation and cell division.…”
Section: Introductionmentioning
confidence: 99%
“…Beans differ from cereals by being quiescent when Al treatment begins and later expressing tolerance components (Cumming et al, 1992;Rangel et al, 2007). That is, beans demonstrate a type II response pattern to Al treatment (Ma et al, 2001), which is characterized by a delay of several hours before organic acids, particularly citric acid, are exuded (Mugai et al, 2000;Shen et al, 2002aShen et al, , 2002bShen et al, , 2004Stass et al, 2007). Recently, Rangel et al (2009) demonstrated that apoplastic Al induces the inhibition of root elongation and that recovery from the stress caused by this element is controlled by reducing Al in the apoplast, thus permitting renewed elongation and cell division.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, decomposition of callose can already occur within 5-10 minutes after tissue injury (Nakashima et al 2003). Plants (including algae) react by increased accumulation of callose also to excess of metals (Bacic et al 2009; Krzes lowska 2011); its rapid deposition in roots upon exposure to aluminium (observable already after less than 1 h) is considered as the most sensitive indicator of this type of stress (Horst et al 1997;Sivaguru et al 2000;Qin et al 2007;Stass et al 2007). Formation of characteristic callose deposits was also observed as a general response of plants to many other metals.…”
Section: Introductionmentioning
confidence: 99%
“…So this complex network of cells makes the cell wall tighter and hinders the entrance of Al into the cell, thus preventing Al contact with cell organelles (O'Neill et al 2004;Corrales et al 2008). Amelioration of Al toxicity by using B has been stated by many researchers in squash (LeNoble et al 1996b), alfalfa (LeNoble et al 1996a), sour pummel (Jiang et al 2009), pea (Yu et al 2009), sunflower (Ruiz et al 2006), common bean (Stass et al 2007), rapeseed (Yan et al 2018), trifoliate (Riaz et al 2018a(Riaz et al , 2018b and however, such an effect was not found by Wang et al (2005) in maize. Many reports have indicated the mechanism behind B-induced alleviation of Al-toxicity, yet the actual mechanism has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Lukaszewski and Blevins (1996) while studying on B-deficient or Al toxic squash plants, proposed that the inhibition of root growth could be a result of a disrupted ascorbate metabolism. Moreover, B-deficiency increased the concentration of un-methylated pectin in the cell wall of roots, creating a more favorable condition for the binding of Al (Stass et al 2007). Additionally, abundant rainfall washes out basic cations from the root zone favoring acidic environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation